Hematemesis in a young patient: When the cause is ingested: A case report - Benayad Aourarh, MD; Lina Belkouchi, MD; Rachida Saouab, MD; Aziz Aourarh, MD; Omar Belkouchi, MD (Radiology Case Reports, 2024)
Foreign bodies may be ingested accidentally or intentionally. Generally, they pass through the digestive tract without causing complications unless they become lodged. Patients often present with nonspecific clinical symptoms, and diagnosis is frequently delayed because they do not recall ingesting anything.We report the case of a 20-year-old man who was admitted to the emergency room for acute moderate hematemesis. The patient had no significant medical history. An urgent, nonsedated upper gastrointestinal (GI) endoscopy was performed, which revealed bleeding but no foreign objects. However, an abdominal CT scan identified a linear calcified object in the antrum, which was later confirmed to be a chicken bone upon endoscopic extraction.Ingested foreign bodies typically pass through the digestive tract without incident. However, long, sharp, and thin objects can remain in the gastrointestinal tract for 7-10 days and may become lodged in areas of physiological narrowing. This can lead to complications such as bowel obstruction, perforation, or bleeding.